Middle Ear Welding Injury: Case Report and Literature Review - Gabriele Bruno; Elena Carlotto; Fabio Bramardi; Elisa Franco; Alessia Lanzillotta; Walter Lerda; Nertila Naqe; Silvia Ponzo (Journal of International Advanced Otology)
Damage to the middle ear (ME) caused by penetrating welding sparks can lead to a variety of adverse outcomes. An exhaustive review of the literature is lacking, particularly with regard to clinical presentation, diagnostic-therapeutic work-up, and outcomes. Here we describe the clinical details of an injury caused by the largest welding foreign body ever reported in the ME. In addition, we present a comprehensive review of the relevant literature.